The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/slct.202000602
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids as the Nitrogen Source to Synthesize Boron Nitride Quantum Dots for Fluorescence Turn‐off‐on Detection of Ascorbic Acid

Abstract: The BNQDs are synthesized by simple one-step hydrothermal method, using amino acids as nitrogen source and boric acid as boron source. The BNQDs prepared by different amino acids emit strong blue fluorescence with the excitation wavelength from 280 to 400 nm. An "on-off-on" BNQDs fluorescent sensor is designed to detect ascorbic acid with Fe 3 + as medium, extending the application in sensing. The fluorescence of BNQDs is quenched by Fe 3 + on basis of the inner filter effect.With increasing of ascorbic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
2
18
1
Order By: Relevance
“…Though the total concentration of both ions can be determined regardless of the oxidation states, detecting individual ions from the mixture is still challenging using this procedure. A similar study for Fe 3+ detection was reported by Kong et al [80].…”
Section: Chemical Sensingsupporting
confidence: 84%
See 2 more Smart Citations
“…Though the total concentration of both ions can be determined regardless of the oxidation states, detecting individual ions from the mixture is still challenging using this procedure. A similar study for Fe 3+ detection was reported by Kong et al [80].…”
Section: Chemical Sensingsupporting
confidence: 84%
“…These BNQDs have an average size of 4 nm and were made by using boric acid and ammonium hydroxide as starting materials. Besides, Kong et al [80] have reported on the hydrothermal synthesis of BNQDs using amino acids (tryptophan) as a nitrogen source and boric acid as a boron source. As compared to other nitrogen precursors, amino acids are high in nitrogen content, good in biocompatibility, and low in price.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The broad absorption bands at 3459−3200 cm −1 were ascribed to the stretching of O−H and N−H. 35 The peak at 1638 cm −1 was assigned to the C−(BN) vibration, which may be induced by the interactions between C atoms and B or N atoms. 26 Furthermore, the characteristic peaks at 1150−850 and 650 cm −1 corresponded to N−B−O and O−B−O bonds, respectively, which demonstrated the oxygen-containing functional groups attached to the surface of BNQDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some nanomaterials and organic molecules can be used as uorescent probes to detect Fe 3+ and AA. [17][18][19][20][21][22] However, these probes are usually difficult to prepare.…”
Section: Introductionmentioning
confidence: 99%